ANCAMAN KEAMANAN JARINGAN PADA SERVER UNTUK MEMBATASI WEBSITE TERTENTU MENGGUNAKAN MIKROTIK - Gunawan, Heri (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2020)
Mikrotik RouterOs â„¢ is an operating system and software that can be used to make a computer a reliable network router, designed to provide convenience for its users, the administration can be done through Windows application (Winbox), The server is a computer system that provides certain types of services (services) in a computer network, the server is supported by a processor that is scalable and a large ram is also equipped with a special operating system, called a (network operating system). The internet provides a lot of useful content if the user uses the internet well, besides that the internet can also have a negative impact on its users if the internet is used for negative things which will affect the young generation who will embrace this country to be the successor of this nation. outside the prevailing norms. Today the internet has many different types of social networking sites that have been used by many people, the goal or One of the solutions is that internet users do not access the negative or self-detrimental effects, using the Scientific of Inquiry method by limiting access to websites Specifically for prevention efforts in accessing negative internet sites in this case containing pornographic content is by blocking these negative sites permanently using a web proxy that serves to block some websites that cannot be accessed by clients through a browser on the Mikrotik Faculty of Engineering routers Ibn Khaldun Universit